Polyarylene sulfide sulfone composite current collector film and preparation method thereof

The polyarylene sulfide sulfone composite current collector film addresses adhesion issues in composite current collectors by using physical modification and additive combinations to enhance bonding strength, improving the safety and mechanical properties of lithium-ion batteries.

CN119239014APending Publication Date: 2025-01-03SICHUAN ZHONGKE XINGYE HIGH-TECH MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411260193.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing composite current collectors face issues with poor adhesion between the non-metallic film and metal foil layers due to surface smoothness and lower surface energy, leading to potential delamination and internal short circuits, which can cause thermal runaway and other adverse phenomena in batteries.

Method used

A method involving the preparation of a polyarylene sulfide sulfone composite current collector film through extrusion casting, biaxial stretching, and physical modification using ultraviolet radiation and plasma treatment to introduce cathode groups, combined with specific additives like phenolic and halogenated hydrocarbon end-capping agents to enhance adhesion, and a two-step copper plating process to ensure strong bonding.

Benefits of technology

The solution improves the mechanical properties and adhesion of the composite current collector, preventing delamination and enhancing the safety of lithium-ion batteries by reducing the risk of thermal runaway and internal short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119239014A_ABST
    Figure CN119239014A_ABST
Patent Text Reader

Abstract

The invention discloses a polyarylene sulfide sulfone composite current collector film and a preparation method thereof, and belongs to the technical field of current collector preparation, the preparation method of the polyarylene sulfide sulfone composite current collector film comprises the following steps: step 1, premixing PASS resin powder with a stabilizer, an antioxidant, a flexibilizer, an anti-sticking agent and a filler, premixing can be carried out in a low-speed mixer, so that uniform dispersion of all auxiliaries is ensured. By improving the preparation materials, the polyarylene sulfide sulfone film is good in high-temperature resistance, corrosion resistance and flame retardance and excellent in impact resistance and tensile resistance, the risk of separation of the conductive copper layer can be effectively avoided by adopting the film, the advantages of excellent flame retardance, heat resistance and the like of polyarylene sulfide sulfone can be exerted, and the film is suitable for large-scale popularization and application. When a current collector is produced and applied to an automobile battery, the phenomenon of thermal runaway easily caused by internal short circuit of a power battery due to a copper layer is relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of current collector preparation, and in particular relates to a polyarylene sulfide sulfone composite current collector film and a preparation method thereof. Background Art

[0002] In the new energy batteries currently made using current collectors, copper foil is selected as the negative electrode current collector. In order to improve energy density and safety, a composite current collector composed of a polymer film and a metal coating has gradually attracted attention. Polyarylene sulfide sulfone (PASS) is a high-performance special engineering material. This material is a structural modification of polyphenylene sulfide (PPS) and has excellent mechanical properties, including high strength and good toughness. It also has good electrical properties and is suitable for electrical and electronic applications. The composite current collector can prevent lithium-ion batteries from catching fire, extrusion, puncture and other abnormal situations due to internal short circuits, resulting in fires, explosions and other accidents.

[0003] The existing Chinese invention patent with patent number CN115477833B discloses that the polyester containing hydroxyl groups at the end and the bridging agent containing hydroxyl groups are used as raw materials, and the electron beam irradiation treatment is used in the process of preparing the modified polyester film to induce the condensation of part of the hydroxyl groups of the polyester and part of the hydroxyl groups in the bridging agent, thereby increasing the molecular weight and crosslinking degree of the polyester, and thus improving the mechanical properties of the modified polyester film. The application of the modified polyester film to the composite current collector can reduce the defective rate caused by film breakage and improve the mechanical properties of the composite current collector. However, after actual operation, because the electron beam irradiation treatment changes the surface properties of the film, the film surface is smooth and basically does not have cathode functional groups, resulting in poor bonding between the conductive copper layer and the non-metallic modified polyester film.

[0004] In battery manufacturing, a composite current collector is usually composed of a non-metallic insulating layer and a metal conductive layer to improve the safety and performance of the battery. However, due to the interface difference between the non-metallic film and the plated metal, the non-metallic film has a lower surface energy and a weaker polarity. This difference leads to a weaker interaction force between the two layers of material, thereby affecting the adhesion. After the non-metallic film is condensed and modified, the surface smoothness increases, and the bonding points with the metal foil layer decrease, which is not conducive to improving the adhesion. When the adhesion between the metal foil layer and the non-metallic base layer is poor, conductive delamination is prone to occur under the action of external force. Once the metal foil layer is squeezed and punctured by external force, it will peel off and fall off, which may cause interlayer short circuit. The interlayer short circuit will aggravate the internal short circuit, thereby causing the battery performance to decline, and even cause thermal runaway and other adverse phenomena. In view of this, a polyarylene sulfide sulfone composite current collector film and a preparation method thereof are provided. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the disadvantages of the prior art and provide a polyarylene sulfide sulfone composite current collector film and a preparation method thereof.

[0006] The technical solution adopted to solve the above technical problems is:

[0007] A method for preparing a polyarylene sulfide sulfone composite current collector film comprises the following steps:

[0008] (1) First, premix the PASS resin powder with stabilizer, antioxidant, toughening agent, anti-sticking agent and filler. The premixing can be carried out in a low-speed mixer to ensure that all additives are evenly dispersed;

[0009] (2) preparing a PASS film by an extrusion casting method: melt-plasticizing polyarylene sulfide sulfone at 200° C. to 350° C. through an extruder, casting a PASS material through a die head, and pulling the PASS material to a casting roller group;

[0010] (3) preparing a PASS film of a specified thickness by biaxial stretching, wherein the thickness of the PASS film is 3 μm ± 0.3 μm;

[0011] (4) The prepared film is physically modified (either ultraviolet radiation treatment or plasma treatment) by introducing hydrogen-, nitrogen- or oxygen-containing gas components to load saturated water vapor into the plasma gas, which can generate a large number of cathode groups on the plastic surface, thereby improving its surface adhesion and facilitating the bonding of the dry adhesive and the material.

[0012] Furthermore, the stabilizer includes a chain extender, a capping agent, and a coupling agent. The stabilizer accounts for 0.1-0.5% of the entire mixture. The chain extender is added in the early stage of the polymerization reaction, the capping agent is added after the chain extender when the polymerization reaction is nearly completed, and the coupling agent is added in the granulation or mixing stage.

[0013] Through the above technical scheme, the chain extender is usually added in the early stage of the polymerization reaction, that is, when the monomer mixture begins to polymerize and the molecular weight is not too high, to improve the strength and toughness of the resin. The end capping agent is added after the desired molecular weight is reached to prevent excessive growth of the polymer chain, which leads to difficulties in subsequent processing. The coupling agent helps to form a chemical bond between the resin and the filler, improves the compatibility and adhesion of the resin with other fillers or reinforcing materials, and improves the mechanical properties and durability of the composite material.

[0014] Furthermore, the end-capping agent is composed of a phenol end-capping agent and a halogenated hydrocarbon end-capping agent, the phenol end-capping agent is p-hydroxybenzoic acid, the halogenated hydrocarbon end-capping agent is halogenated benzene, and the mass ratio of p-hydroxybenzoic acid to halogenated benzene is 1:2.

[0015] Through the above technical scheme, when phenolic end-capping agents and halogenated hydrocarbon end-capping agents are used in combination, there are not only hydrogen bonds and dipole-dipole interactions between the polymer chains, but also other types of intermolecular forces such as van der Waals forces, which make the cohesion between the polymer chains stronger and the structure of the polymer chains more stable, which helps to improve the mechanical properties and thermal stability of the polymer.

[0016] Furthermore, the antioxidant accounts for 0.1-0.5% of the entire mixture, and the antioxidant is a phenolic antioxidant, and the phenolic antioxidant is one or more of tert-butylhydroquinone, 2,6-di-tert-butyl-4-methylphenol and 2,6-di-tert-butyl-p-cresol.

[0017] Through the above technical solution, during the melting process, the oxidation process is prevented by capturing free radicals, thereby preventing the resin from being aged due to heat.

[0018] Furthermore, the antioxidant is a combination of a phenolic antioxidant and a metal chelating agent, and the metal chelating agent is one or more of citric acid, phosphoric acid and ascorbic acid.

[0019] Through the above technical solution, metal ion oxidation is resisted during the resin preparation process, and the subsequent unreacted metal chelating agent forms a stable complex with metal copper ions during the electroplating of the metal layer, thereby improving the firmness of the bonding.

[0020] Furthermore, the toughening agent accounts for 0.2-1% of the entire mixture, and the toughening agent is one or more of polystyrene-butadiene-styrene copolymer (SBS), polypropylene-butadiene-styrene copolymer (PBS), polymethyl methacrylate (PMMA), polycarbonate (PC) and polyimide (PI).

[0021] Through the above technical scheme, these toughening agents can reduce the adhesion of resin on processing equipment during the preparation stage and improve the fluidity during mixing. They can also introduce cathode groups during the subsequent metal plating process to improve the bonding strength between the non-metallic base layer and the metal copper layer.

[0022] Furthermore, the anti-adhesive agent can be one or more of polydimethylsiloxane (PDMS), calcium stearate, methyl stearate and polyvinyl alcohol (PVA), and the anti-adhesive agent accounts for 0.1-0.5% of the whole mixture. The filler can be selected from microporous particles and nanoparticles, and the filler accounts for 1-5% of the whole mixture.

[0023] Through the above technical solution, the anti-sticking agent prevents the resin particles from sticking to each other. The microporous particles and nanoparticles have a large surface area, which can supplement the weak areas between the resin molecules and enhance the toughness of the polymer itself. They are used to improve physical properties, increase tensile strength, and control costs.

[0024] Furthermore, in step 4, plasma treatment and ultraviolet radiation treatment are simultaneously performed for physical modification.

[0025] Through the above technical scheme, combined with ultraviolet radiation treatment and plasma treatment, more abundant functional groups can be introduced on the polymer surface, and coordination compounds can be formed to more effectively improve the surface adhesion of the polymer film.

[0026] A polyarylene sulfide sulfone composite current collector film comprises a base layer, the base layer is a film structure made by casting and stretching polyarylene sulfide sulfone resin, and an adhesion layer is generated on the surface of the base layer through physical modification.

[0027] Through the above technical solution, the adhesion layer is produced by physical modification and is used to provide a good adhesion environment for the copper plating layer.

[0028] A method for preparing a polyarylene sulfide sulfone composite current collector, comprising a polyarylene sulfide sulfone composite current collector film, and the specific steps are as follows:

[0029] (1) obtaining the polyarylene sulfide sulfone composite current collector film of the desired thickness by a conventional composite current collector preparation method, such as using a two-step method of magnetron sputtering plus evaporation / water electroplating to plate copper on the PASS base film, first sputtering a conductive metal layer on the surface of the PASS base film, and then using evaporation or water electroplating to deposit copper ions on the PASS base film to form a conductive film;

[0030] (2) A composite current collector prepared with PASS film as the base film is obtained.

[0031] A polyarylene sulfide sulfone composite current collector is prepared by a polyarylene sulfide sulfone composite current collector preparation method. A copper layer is sputtered on an attachment layer on the surface of a base layer, and the thickness of the attachment copper layer increases to form a metal film.

[0032] Through the above technical scheme, copper is plated on the PASS base film using a two-step method of magnetron sputtering plus evaporation / water electroplating. First, a layer of conductive metal film is sputtered on the surface of the PASS base film, and then evaporation or water electroplating is used to deposit copper ions on the PASS base film to form a thin film, thereby obtaining a conductive copper layer with uniform thickness in steps.

[0033] The beneficial effects of the present invention are as follows:

[0034] (1) The present invention improves the preparation material, and the polyarylene sulfide sulfone film is resistant to high temperature, corrosion, and flame retardant, and is also excellent in impact resistance and tensile resistance. The use of the film can effectively avoid the risk of separation of the conductive copper layer, and can also give full play to the advantages of the excellent flame retardancy and heat resistance of polyarylene sulfide sulfone. When the current collector is produced and applied to automotive batteries, the phenomenon of thermal runaway caused by internal short circuits in the power battery due to the copper layer is alleviated;

[0035] (2) The present invention optimizes the preparation process and selects a combination of a phenolic end-capping agent and a halogenated hydrocarbon end-capping agent to introduce multiple polar interactions, synergistic effects and a stable molecular structure into the PASS film, thereby further increasing the tensile strength of the finished resin. The selected toughening agent reduces adhesion to the equipment during the resin pulling process, and a variety of functional groups can be introduced in the physical modification to improve the bonding strength between the non-metallic base layer and the metal copper layer.

[0036] (3) The present invention improves the preparation process and utilizes physical modification to generate a large number of cathode groups on the surface of the PASS film before sputtering copper plating. The cathode groups generated are diversified through a combination of ultraviolet radiation treatment and plasma treatment, and different types of chemical bonds and compounds are generated between the cathode groups and the metal ions, thereby improving the surface adhesion and further enhancing the bonding strength between the base layer and the copper layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Schematic diagram of the structure of the polyarylene sulfide sulfone composite current collector film of the present invention;

[0038] Figure 2 Schematic diagram of the structure of the polyarylene sulfide sulfone composite current collector of the present invention;

[0039] Figure 3 is a flow chart for preparing the polyarylene sulfide sulfone composite current collector film of the present invention;

[0040] Figure 4 It is a schematic diagram of the process of the polyarylene sulfide sulfone composite current collector of the present invention.

[0041] Figure numerals: 1. base layer; 2. adhesion layer; 3. adhesion copper layer; 4. metal film. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0043] Embodiment 1

[0044] In this embodiment, a method for preparing a polyarylene sulfide sulfone composite current collector film is provided. The preparation of film-grade polyarylene sulfide sulfone (PASS) resin particles involves converting a powdered resin into a particle form suitable for film processing. In this process, a variety of additives can be added to improve the processing properties of the resin and the properties of the final film. The following are the raw materials in the preparation process, the proportion of each raw material, and the detailed steps:

[0045] Ingredients needed:

[0046] PASS resin powder: as the basic raw material, accounting for 95-99% (mass ratio) of the whole mixture, stabilizer: prevent the degradation of the resin during processing, accounting for 0.1-0.5% of the whole mixture, antioxidant: prevent the oxidation of the resin during high temperature processing, accounting for 0.1-0.5% of the whole mixture, toughening agent: reduce the adhesion of the resin on the processing equipment and improve the fluidity, accounting for 0.2-1% of the whole mixture, anti-sticking agent: prevent the adhesion between the resin particles, accounting for 0.1-0.5% of the whole mixture, filler (optional microporous particles, nanoparticles, etc.) accounts for 1-5% of the whole mixture, nanoparticles can be dispersed in the resin matrix as a reinforcing phase due to their high specific surface area and surface activity, and improve the strength and stiffness of the material by increasing the interface area. For example, carbon nanotubes, nanoclays, silica nanoparticles, etc. are often used to reinforce resins, and microporous particles can increase the specific strength and specific stiffness of the material by forming a composite material with a regular pore structure, that is, the strength and stiffness per unit weight.

[0047] Reference Figure 1 , the specific steps are as follows:

[0048] (1) First, premix the PASS resin powder with stabilizer, antioxidant, toughening agent, anti-sticking agent and filler. The premixing can be carried out in a low-speed mixer to ensure that all additives are evenly dispersed;

[0049] (2) preparing a PASS film by an extrusion casting method: melt-plasticizing polyarylene sulfide sulfone at 200° C. to 350° C. through an extruder, casting a PASS material through a die head, and pulling the PASS material to a casting roller group;

[0050] (3) preparing a PASS film of a specified thickness by biaxial stretching, wherein the thickness of the PASS film is 3 μm ± 0.3 μm;

[0051] (4) The prepared film is physically modified (either ultraviolet radiation treatment or plasma treatment) by introducing hydrogen-, nitrogen- or oxygen-containing gas components to load saturated water vapor into the plasma gas, which can generate a large number of cathode groups on the plastic surface, thereby improving its surface adhesion and facilitating the bonding of the dry adhesive and the material.

[0052] Embodiment 2

[0053] Stabilizers include chain extenders, end-capping agents, and coupling agents. Chain extenders are usually used to increase the molecular weight of polymers, improve their mechanical properties and heat resistance. Chain extenders are usually added in the early stages of the polymerization reaction, that is, when the monomer mixture begins to polymerize and the molecular weight is not too high, to improve the strength and toughness of the resin, improve the uniformity of the molecular chain, and reduce the molecular weight distribution.

[0054] End-capping agents are used to terminate the polymerization reaction and prevent the polymer chain from growing further. End-capping agents are usually added when the polymerization reaction is close to completion, that is, added during the polymerization stage. After the desired molecular weight is reached, the end-capping agents prevent the polymer chain from growing excessively, which leads to difficulties in subsequent processing. After the polymerization is completed, end-capping agents can also be used as stabilizers to improve the thermal stability of the finished resin.

[0055] Coupling agents are used to improve the bonding performance of resins and other materials, especially in the preparation of composite materials. Coupling agents are added in the later stage of polymerization in the preparation of resin particles, that is, in the granulation or mixing stage, which helps to form chemical bonds between resin and filler, improve the compatibility and bonding strength of resin with other fillers or reinforcing materials, and improve the mechanical properties and durability of composite materials.

[0056] Embodiment 3

[0057] The combination of phenolic end-capping agent (parahydroxybenzoic acid) and halogenated hydrocarbon end-capping agent (halogenated benzene) in a ratio of 1:2 can improve the polarity of the polymer and the adhesion to other materials, thereby improving the tensile properties of the finished product, while other factors remain unchanged. This effect is stronger than using one of the end-capping agents alone. The specific reasons are as follows:

[0058] First, the hydroxyl group (-OH) in p-hydroxybenzoic acid is a strongly polar functional group that can form hydrogen bonds with other functional groups or the main chain on the polymer chain. This hydrogen bond is a relatively strong intermolecular force that helps to increase the polarity of the polymer. The halogen atoms (such as chlorine or bromine) in halogenated benzene carry partial charges and can produce dipole-dipole interactions. Although this interaction is not as strong as hydrogen bonds, it also significantly increases the polarity of the polymer. When two capping agents exist at the same time, their respective polar effects can be superimposed, thereby producing a stronger polar effect at the molecular level.

[0059] Secondly, when a phenolic end-capping agent or a halogenated hydrocarbon end-capping agent is used alone, only one type of polar interaction can be generated. However, when the two are used in combination, a synergistic effect can be generated, that is, the polar effect of one end-capping agent can enhance the polar effect of another end-capping agent. This synergistic effect makes the polar sites on the polymer chain more abundant, thereby enhancing the overall polarity of the polymer.

[0060] Afterwards, when the phenolic end-capping agent and the halogenated hydrocarbon end-capping agent are used in combination, there are not only hydrogen bonds and dipole-dipole interactions between the polymer chains, but also other types of intermolecular forces such as van der Waals forces. These multiple types of forces work together to make the cohesion between the polymer chains stronger. Due to the enhancement of the intermolecular forces, the structure of the polymer chains is more stable, which helps to improve the mechanical properties and thermal stability of the polymer. The stable molecular structure enables the polymer to more effectively transmit and disperse the forces when in contact with other materials, thereby improving the adhesion.

[0061] Finally, when the polymer comes into contact with other materials, the hydroxyl groups of the phenolic end-capping agents and the halogen atoms of the halogenated hydrocarbon end-capping agents can form strong interfacial interactions with the functional groups on the surface of the other material. These interactions help to form a stable interface between the polymer and the bonding material. The phenolic end-capping agents and the halogenated hydrocarbon end-capping agents react chemically with the surface of the bonding material to form covalent bonds. The formation of covalent bonds is more stable than simple physical adsorption (such as hydrogen bonds, dipole-dipole interactions), and can therefore provide a more durable bonding effect.

[0062] In summary, the combined use of phenolic capping agents and halogenated hydrocarbon capping agents improves the polarity of the polymer and the adhesion to other materials by introducing multiple polar interactions, synergistic effects, rich interaction types and stable molecular structures, as well as interfacial interactions and the formation of chemical bonds at the molecular level, thereby increasing the toughness of the finished resin and further improving the tensile properties of the finished resin. The effect of this combination is more significant than using one of the capping agents alone.

[0063] Embodiment 4

[0064] The antioxidant uses phenolic antioxidants (tert-butyl hydroquinone, 2,6-di-tert-butyl-4-methylphenol, 2,6-di-tert-butyl-p-cresol) as antioxidants. During the melting process, the oxidation process is prevented by capturing free radicals. The antioxidant accounts for 0.1-0.5% of the entire mixture.

[0065] Embodiment 5

[0066] Metal chelating agents (citric acid, phosphoric acid and ascorbic acid) are added to supplement the resistance to metal ion oxidation. The unreacted metal chelating agents subsequently form stable complexes with metal copper ions during the electroplating of the metal layer, thereby improving the firmness of the joint.

[0067] Embodiment 6

[0068] Tougheners account for 0.2-1% of the entire mixture and are used to reduce the adhesion of the resin on the processing equipment and improve the fluidity of the mixture. The following specific tougheners can be selected to improve the bonding strength between the non-metallic base layer and the metal copper layer during the subsequent metal plating process while other factors remain unchanged:

[0069] 1. Polystyrene-butadiene-styrene copolymer (SBS): SBS is a thermoplastic elastomer, which contains styrene and butadiene units in its molecular structure. Through plasma treatment or ultraviolet radiation treatment, functional groups such as hydroxyl and carboxyl can be introduced. These functional groups can form chemical bonds with metal ions, thereby improving the bonding strength with metal ions;

[0070] 2. Polypropylene-butadiene-styrene copolymer (PBS): PBS is also a thermoplastic elastomer. Its molecular structure contains polypropylene, butadiene and styrene units. Through plasma treatment or ultraviolet radiation treatment, functional groups such as hydroxyl and carboxyl can be introduced. These functional groups can form chemical bonds with metal ions, thereby improving the binding strength with metal ions.

[0071] 3. Polymethyl methacrylate (PMMA): PMMA is a transparent thermoplastic polymer, which contains methyl methacrylate units in its molecular structure. Through plasma treatment or ultraviolet radiation treatment, functional groups such as hydroxyl and carboxyl can be introduced. These functional groups can form chemical bonds with metal ions, thereby increasing the bonding strength with metal ions;

[0072] 4. Polycarbonate (PC): PC is a transparent thermoplastic polymer, which contains carbonate units in its molecular structure. Through plasma treatment or ultraviolet radiation treatment, functional groups such as hydroxyl and carboxyl can be introduced. These functional groups can form chemical bonds with metal ions, thereby improving the bonding strength with metal ions;

[0073] 5. Polyimide (PI): PI is a highly heat-resistant polymer whose molecular structure contains imide units. Through plasma treatment or ultraviolet radiation treatment, functional groups such as hydroxyl and carboxyl can be introduced. These functional groups can form chemical bonds with metal ions, thereby increasing the binding strength with metal ions.

[0074] Embodiment 7

[0075] The anti-adhesive agent can be one or more of polydimethylsiloxane (PDMS), calcium stearate, methyl stearate and polyvinyl alcohol (PVA) to prevent the resin particles from sticking to each other. The anti-adhesive agent accounts for 0.1-0.5% of the whole mixture. The filler can be microporous particles, nanoparticles, etc., which are used to improve physical properties and tensile strength, accounting for 1-5% of the whole mixture.

[0076] Embodiment 8

[0077] Plasma treatment and ultraviolet radiation treatment are carried out simultaneously, wherein the high-energy particles in the plasma hit the polymer surface, causing the molecular chains to break and form hydroxyl groups. These functional groups are formed on the surface of the base layer. The ultraviolet rays have enough energy to excite the electrons in the molecules. The double bonds, hydroxyl groups and other functional groups in the molecules can be broken to form carbonyl groups, thereby changing the surface properties;

[0078] When ultraviolet radiation treatment and plasma treatment are used in combination, hydrogen-, nitrogen- or oxygen-containing gases can be introduced. Hydrogen can react with the polymer surface to form hydrogen bonds, nitrogen can react with the polymer surface to form amino groups, and oxygen-containing gases can react with the polymer surface to form carbonyl or carboxyl groups, thereby improving surface adhesion.

[0079] It should be emphasized that UV radiation treatment and plasma treatment can produce a synergistic effect. UV radiation treatment is more inclined to introduce hydroxyl groups (-OH). The combination of hydroxyl groups and metal ions is more stable than that of carbonyl groups. This is because when the oxygen atoms in the hydroxyl groups combine with metal ions, the electron cloud distribution of the hydroxyl groups is more conducive to forming a stable coordination bond, and the hydrogen atoms of the hydroxyl groups can form additional hydrogen bonds with the metal ions, thereby enhancing the binding force. Plasma treatment can introduce carboxyl groups (-COOH) and carbonyl groups (-CO-) on the basis of hydroxyl groups (-OH), and the lone pair is provided by the ligand (such as the oxygen atoms in the hydroxyl groups). Electrons, while metal ions provide empty orbitals. This bonding mode is a covalent bond, but different from general covalent bonds, it involves electron sharing between metal ions and ligands to form coordination compounds, which can further improve the bonding strength. That is, ultraviolet radiation treatment can provide the introduction of hydroxyl groups (-OH), which provides sufficient hydroxyl groups (-OH) for ion treatment to introduce carboxyl groups (-COOH) and carbonyl groups (-CO-). Combining these two technologies can introduce more abundant functional groups on the polymer surface. Through the treatment of these two technologies, more stable functional groups can be formed on the polymer surface, thereby improving surface adhesion.

[0080] In summary, under the premise that other factors remain unchanged, the combination of ultraviolet radiation treatment and plasma treatment can more effectively improve the surface adhesion of the polymer film, which is beneficial to the bonding of the conductive copper layer and the base layer.

[0081] Embodiment 9

[0082] like Figure 2As shown, this embodiment provides a polyarylethersulfidesulfone composite current collector film, including a base layer 1, the base layer 1 is a film structure made of polyarylethersulfidesulfone resin by casting and stretching, the resin is extruded into a film sheet in a casting unit after twin-screw extrusion granulation, and then stretched horizontally and longitudinally in a bidirectional film-drawing machine to prepare a film with uniform thickness, the preparation of the polyarylethersulfone film requires the use of extrusion casting method, stretching method or film blowing method, these methods have high requirements on processing equipment, in the casting process, the polyarylethersulfone resin solution is diluted and mixed, and then coated on the substrate, and film is formed by solution casting method, the traction rate, drying temperature zone, drying temperature , hot air temperature and wind speed are all parameters that need to be controlled. For example, the traction rate can be between 0.02-2.00m / min, the drying temperature can be controlled at 20-240℃, the thickness of the prepared base layer 1 is 3μm, and an error of 0.3μm is allowed. In order to facilitate the subsequent adhesion of the conductive copper layer, the base layer 1 needs to be modified. The modification method is to introduce a large number of cathode groups on the surface of the base layer 1, that is, the surface of the base layer 1 is physically modified to produce an adhesion layer 2. The adhesion layer 2 can be retained for a period of time, and when the copper ions are subsequently attached, it can adsorb copper ions and undergo bonding reactions with the copper ions.

[0083] Embodiment 10

[0084] like Figure 3 As shown, this embodiment provides a method for preparing a polyarylene sulfide sulfone composite current collector, comprising the following steps:

[0085] (1) Using PASS film as the base film, a polyarylene sulfide sulfone composite current collector film is obtained by a conventional composite current collector preparation method, which mainly includes two steps: magnetron sputtering and water electroplating. First, a metal layer is plated on the surface of the plastic film by magnetron sputtering (PVD). The metal layer is about 15-40 nanometers thick to ensure conductivity and the density and bonding strength of the film layer. Next, the metal layer is thickened by water electroplating to make the entire current collector reach a thickness of 6.5 microns. During the process, the magnetron sputtering equipment is used for the deposition of the initial metal layer, while the water electroplating equipment is used for the subsequent thickening of the metal layer. The magnetron sputtering equipment needs to accurately control various parameters in the sputtering process, such as sputtering power, gas pressure, etc., to ensure the uniformity and quality of the metal layer. The water electroplating process needs to pay attention to factors such as the composition, temperature, and current density of the plating solution to ensure the quality and uniformity of the coating.

[0086] Composite current collectors, such as composite copper foil, are formed by plating a certain thickness of copper layer on both sides of the polymer material layer to form a composite structure similar to a "sandwich". This structure can significantly reduce the material cost and weight of the current collector, while improving the energy density and safety of the battery. After years of development and iteration, the composite current collector industry has significantly optimized its processes and equipment, and gradually has mass production capacity. At present, some leading current collector companies have been able to achieve initial mass production, and their yield and production efficiency are still being optimized. The specific equipment model, process parameters (such as temperature, time) and detailed process may vary according to different production requirements and material properties, that is, first sputter a conductive metal layer on the surface of the PASS base film, and then use evaporation or water electroplating methods to deposit copper ions on the PASS base film to form a conductive film;

[0087] (2) A composite current collector prepared with PASS film as the base film is obtained.

[0088] Embodiment 11

[0089] like Figure 4 As shown, a polyarylene sulfide sulfone composite current collector, the adhesion layer 2 on the surface of the base layer 1 is sputtered to obtain an adhesion copper layer 3, and the thickness of the adhesion copper layer 3 is increased to form a metal film 4, which is carried out step by step, which can ensure that the copper ions in the early stage can be smoothly attached to the base layer 1, and can also ensure that the thickness of the metal film 4 is uniform.

[0090] Performance testing:

[0091] Thickness detection of PASS film

[0092] PASS film thickness uniformity test

[0093] Dielectric constant measurement of PASS film

[0094] PASS film tensile performance test PASS film heat resistance test Composite current collector thickness test Composite current collector surface density test Composite current collector oxidation resistance test Composite current collector tensile strength test Composite current collector adhesion test Composite current collector square resistance test Composite current collector electronic stripping test Composite current collector dyne value test

[0095]

[0096]

[0097]

[0098] By comparison with specific embodiments, the data of Embodiment 1 shows that, through testing, the finished product has excellent heat resistance, there is no shedding between the base layer and the copper layer, and it fully meets the use requirements; after optimizing the end-capping agent in Embodiment 3, the pulling performance of the film is significantly improved, indicating that the combination of end-capping agents can optimize the tensile strength of the film; in Embodiment 6, the composite current collector with a higher dyne value can reduce the separation between the copper layer and the base layer. The data show that the surface density of the current collector increases, the dyne value increases, and the cathode group is introduced by the toughening agent, which can further improve the binding ability of the copper layer to the base layer on the basis of physical modification; in Embodiment 8, the data show that it is not much different from Embodiment 6, but the dyne value is further slightly increased. During the physical modification treatment, the cathode group is introduced by combining the two modification methods, and more coordination bonds, covalent bonds and coordination compounds with metal ions are generated, which can further improve the binding strength, thereby improving the electrochemical performance and safety of the battery.

[0099] In summary, in this scheme, PASS membrane is used to replace the traditional membrane method. The polyarylether sulfide sulfone film not only has the advantages of high temperature resistance, corrosion resistance, and good flame retardancy, but also has excellent mechanical properties such as impact resistance and bending resistance. Therefore, the use of this film in the preparation of the composite current collector can effectively avoid the risk of detachment of the conductive foil layer, and can also give play to the excellent flame retardancy and heat resistance of polyarylether sulfide sulfone. The advantages, such as the innovation of materials and structures, alleviate the industry pain point of thermal runaway caused by internal short circuits in power batteries, and break through the technical bottleneck of traditional internal short circuit protection technology that is difficult to take into account the battery's specific energy, light weight and other performance. At the same time, the strong compatibility of high-performance composite current collectors has greatly accelerated the iteration speed of power battery performance, and is one of the best solutions for high-end customized power batteries. Its broad application prospects will lead the innovation of power battery technology worldwide.

[0100] The above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention.

Claims

1. A method for preparing a polyarylene sulfide sulfone composite current collector film, characterized in that: The steps include: Step 1: First, premix the PASS resin powder with stabilizer, antioxidant, toughening agent, anti-sticking agent and filler in a low-speed mixer; Step 2: preparing a PASS film by an extrusion casting method: melt-plasticizing polyarylene sulfide sulfone at 200° C. to 350° C. through an extruder, casting a PASS material through a die head, and pulling the PASS material to a casting roller group; Step 3: Prepare a PASS film with a required thickness by biaxial stretching, and the thickness of the PASS film is 3 μm ± 0.3 μm; Step 4: The prepared film is physically modified by using one of ultraviolet radiation treatment and plasma treatment to introduce hydrogen-containing, nitrogen-containing or oxygen-containing gas components, load saturated water vapor into the plasma gas, and generate a large number of cathode groups on the plastic surface.

2. The polyarylene sulfide sulfone composite current collector film according to claim 1, characterized in that: The stabilizer comprises a chain extender, an end capping agent and a coupling agent, wherein the stabilizer accounts for 0.1-0.5% of the entire mixture, the chain extender is added in the early stage of the polymerization reaction, the end capping agent is added after the chain extender when the polymerization reaction is nearly completed, and the coupling agent is added in the granulation stage.

3. The method for preparing the polyarylene sulfide sulfone composite current collector film according to claim 2, characterized in that: The end-capping agent is composed of a phenol end-capping agent and a halogenated hydrocarbon end-capping agent. The phenol end-capping agent is p-hydroxybenzoic acid, and the halogenated hydrocarbon end-capping agent is halogenated benzene. The mass ratio of p-hydroxybenzoic acid to halogenated benzene is 1:

2.

4. The method for preparing the polyarylene sulfide sulfone composite current collector film according to claim 1, characterized in that: The antioxidant accounts for 0.1-0.5% of the whole mixture. The antioxidant is a phenolic antioxidant, and the phenolic antioxidant is one or more of tert-butyl hydroquinone, 2,6-di-tert-butyl-4-methylphenol and 2,6-di-tert-butyl-p-cresol.

5. The method for preparing the polyarylene sulfide sulfone composite current collector film according to claim 1, characterized in that: The antioxidant is a combination of a phenolic antioxidant and a metal chelating agent, and the metal chelating agent is one or more of citric acid, phosphoric acid and ascorbic acid.

6. The method for preparing the polyarylene sulfide sulfone composite current collector film according to claim 1, characterized in that: The toughening agent accounts for 0.2-1% of the whole mixture, and the toughening agent is one or more of polystyrene-butadiene-styrene copolymer, polypropylene-butadiene-styrene copolymer, polymethyl methacrylate, polycarbonate and polyimide.

7. The method for preparing the polyarylene sulfide sulfone composite current collector film according to claim 1, characterized in that: In the step 4, plasma treatment and ultraviolet radiation treatment are simultaneously performed to perform physical modification.

8. A polyarylene sulfide sulfone composite current collector film, obtained according to the method for preparing a polyarylene sulfide sulfone composite current collector film according to any one of claims 1 to 7, characterized in that: The invention comprises a base layer (1), wherein the base layer (1) is a film-like structure made by casting and stretching polyarylene sulfide sulfone resin, and an adhesion layer (2) is generated on the surface of the base layer (1) through physical modification.

9. A method for preparing a polyarylene sulfide sulfone composite current collector, comprising the polyarylene sulfide sulfone composite current collector film according to claim 8, characterized in that: The steps include: Step 1: obtain the polyarylene sulfide sulfone composite current collector film of the desired thickness by a conventional composite current collector preparation method, and plate copper on the PASS base film by two-step magnetron sputtering plus evaporation / water electroplating, first sputter a conductive metal layer on the surface of the polyarylene sulfide sulfone composite current collector film, and then use evaporation or water electroplating to deposit copper ions on the polyarylene sulfide sulfone composite current collector film to form a conductive film; Step 2: Obtain a composite current collector prepared using a polyarylene sulfide sulfone composite current collector film as a base film.

10. A polyarylene sulfide sulfone composite current collector, prepared by the method for preparing a polyarylene sulfide sulfone composite current collector according to claim 9, characterized in that: A copper layer (3) is sputtered onto an adhesion layer (2) on the surface of a base layer (1), and the thickness of the adhesion copper layer (3) is increased to form a metal film (4). The finished product is applied to automobile batteries.